RELEVANSI PROGRAM ASEAN Economic Community (AEC) DENGAN KEBIJAKAN PEMERINTAH DALAM MENINGKATKAN PEREKONOMIAN DAN SUMBER DAYA MANUSIA DI BIDANG PARIWISATA DI INDONESIA - Siti Shindy Revani; Abdul Rahman; Arif Arif (Journal of USU International Law, 2018)
ABSTRACT *) Siti Shindy Revani **) Abdul Rahman, SH., M.H ***) Arif, SH., M.H Globalization requires ASEAN to create regional integration in Southeast Asia, one of the main pillars of ASEAN Vision 2020 is the ASEAN Economic Community (AEC) where one of its fields is Tourism.The problem that will be raised in this research is how to regulate the ASEAN Economic Community (AEC) in ASEAN regional organizations, form of cooperation in the Tourism sector within the scope of the ASEAN Economic Community (AEC) and also ASEAN Economic Community (AEC) program in Tourism sector in economic development and Human Resources in Indonesia. The purpose of this research was to determine the arrangements regarding AEC in ASEAN regional organizations, forms of cooperation in the of Tourism within the scope of the AEC and AEC program in Tourism sector in economic development and Human Resources in Indonesia. In this writing is a normative legal research. The data obtained and processed in this research are secondary data derived from library sources and then data were analyzed with qualitative descriptive. The results of this research shows that the arrangement of the ASEAN Economic Community (AEC) in ASEAN regional organizations cannot stand alone where it becomes a package of regionalism policies.The form of ASEAN Economic Community cooperation in the Tourism sector are between Indonesia and Singapore by signing the Memorandum of Understanding (MoU) on Tourism Indonesia-Singapore and between Indonesia and Vietnam is The Joint Commission Indonesia-Vietnam on Economic, Scientific and Technical Cooperation (JCESTC). The AEC program in the Tourism sector in economic development and Human Resources with promoting tourism programs, improving infrastructure and improving human resources through education and training. Keywords: Tourism, Economics, Human Resources,  ASEAN Economic Community     *) Law Studentof University of Sumatera Utara **) Counsellor I ***) Counsellor II